Absorption of creatine supplied as a drink, in meat or in solid form - Harris, R.C.; Nevill, M.; Harris, D.B.; Fallowfield, J.L.; Bogdanis, G.C.; Wise, J.A. (Journal of Sports Sciences, 2002)
We examined the plasma concentration curve obtained over 6 h after the ingestion of 2 g of creatine (Cr) (equivalent to 2.3 g Cr·H2O) contained in meat or in solution in five non-users of creatine supplements. Peak plasma creatine concentration was lower after the ingestion of meat but was maintained close to this for a longer period. Measurements of the area under the plasma concentration curve indicated approximate bioequivalence of creatine contained in meat with the same dose supplied in a solution. In a separate study, we examined the plasma concentration-time curve after ingestion of solid Cr·H2O. Creatine ingested as a lozenge (crushed in the mouth and swallowed) or as a crystalline suspension in ice cold water resulted in a 20% lower peak concentration and 30-35% smaller area under the plasma creatine concentration curve than the same dose administered in solution. Despite a possibly lower bioavailability, 2.3 g Cr·H2O supplied in either solid form was nonetheless sufficient to raise the plasma concentration five- to six-fold in individuals with a mean body mass of 75.6 kg. We conclude that creatine administered as meat or in solid form is readily absorbed but may result in sligthly lower peak concentrations than when the same dose is ingested as a solution.